COLLABORATION OF SCHOOL COMMITTEE ASSOCIATIONS FOR THE GREAT GENERATION OF PANCASILA STUDENTS BASED ON GREAT PARENTING SCHOOLS AT STATE PRIMARY SCHOOL 1 HUNGAYONAA VILLAGE, BOALEMO DISTRICT - Novianty Djafri; Sukma Nurilawati Botutihe, Isnanto (International Journal of Teaching and Learning, 2025)
The general goal is to produce a generation of character who is not only intellectually and technologically intelligent, but also has strong moral and spiritual strength based on religious and cultural values in society, in accordance with the program's vision and mission and the goals of Indonesian education, so that schools can realize the participants students with character who understand the values of Pancasila and culture in the era of independence learn by realizing an advanced Indonesia that is sovereign, independent, and has personality through the creation of Pancasila students. The specific aim of the service is to carry out mentoring and strengthen the school principal's strategy in collaborating with school committee associations for a great generation of Pancasila students based on great parents (SOTH Parenting at the Hungayonaa Village 1 Elementary School, Boalemo Regency. The service method used is a survey with a descriptive qualitative approach, namely narrates the description of the results of service activities using descriptive analysis.The results of the service are the implementation of mentoring and strengthening activities through the implementation of education and training activities (Training/FGD/Seminars) Mentoring Strengthening School Principal Strategies in Collaboration with School Committee Associations for the Great Generation of Pancasila Students Based on Schools Great Parents (SOTH Parenting), which is oriented towards the benefits of ; 1) Socialization of the SOTH Parenting program to parents, the community (school committee) and the community of the Great Parents School program (SOTH Parenting) 2) Implementation of Education and training to Strengthen School Principal Strategies,3) implementation of assistance from the School Committee/parents who are part of the program (SOTH Parenting) and the community environment around the school for their children as the Great Generation of Pancasila Students; attended by the surrounding community 4) Grand Design of the School Model for Great Parents (SOTH Parenting),produce a generation that is not only intellectually and technologically intelligent, but also has strong moral and spiritual strength based on the values of character education and culture of their respective regions, thus, this great generation is expected to be able to face the challenges of the modern era based on the values good character values by mastering and using knowledge and technology well and wisely.